Pengaruh Bauran Promosi Terhadap Keputusan Pembelian Konsumen Pada Perusahaan Jamu Dayang Sumbi Mojokerto - NORINDA SARI, KURNIA (Jurnal Pendidikan Tata Niaga (JPTN), 2014)
Competition in the industry of herbal medicine tends to increase. Dayang Sumbi as a manufacturer of herbal medicine should be able to compete by offering quality herbal medicine and can satisfy consumer desire. In marketing its product of Dayang Sumbi, herbal medicine needs to haves media between consumer and company that is through promotion as the communication media between company and consumer. In order the promotion can interest the attention and influence consumer in buying, so the company does promotional mix that implies several variables those are advertisement, sales promotion, public relation, personal selling and direct marketing. The result of this research shows promotion mixture stimulatingly has significance influence on herbal medicine buying decision Dayang Sumbi Mojokerto (Y). This can be proved by the testing measure F is obtained Fhitung 28,888 with the p value amount 0,000 _ 0,05. Besides that, Adjusted R Square amount 0,618 it means that the free variable influence on bounded variable is 61,8%. And the testing t is found that partially free variable influences significantly. And the most dominant variable influencing on herbal medicine buying decision Dayang Sumbi Mojokerto is direct marketing variable (X5) that is amount 3,184 Keyword : Promotion Mixture, Purchasing Decision